(untitled) (Physical Education, Health and Social Sciences, 2025)
This research is based on fabrication of iron oxide thin films on fluorine doped tin oxide (FTO) substrate having (dimensions 40 x 40 x 2mm) using ferrocene precursor by applying pyrolysis method. We employed ferrocene precursor and prepared a sample slide denoted as S-1, To ensure even dispersion of iron oxide thin films with clear morphology and controlled particle size distribution, which effectively increases the surface area of the FTO substrates and thus catalytic ability. Thin film was fabricated using accurate masses of ferrocene (0.125 g) in small crucible, finally ferrocene was thermally decomposed at 500 °C for 30 minutes in an electric furnace. The Scanning Electron Microscopy (SEM), was brought into action to analyze surface morphology of thin films, which confirmed a successful homogeneous distribution of iron oxide thin film on FTO. Energy Dispersive X-ray Spectroscopy (EDS) was used to investigate elemental analysis, which authenticated existence of iron (Fe) and oxygen (O) as principal elements, verifying enhanced purity and productive adsorption of iron oxide onto the FTO substrate. Finally, catalytic activity of thin film (S-1) was investigated through Methylene Blue (MB) dye degradation in the presence of sunlight, exhibiting their significant potential for environmental decontamination and catalytic activity. Sample slide S-1 showed catalytic ability with 40% effective degradation.